Bond between glulam and NSM CFRP laminates - Sena-Cruz, José (2013)
With the aim of evaluating the bond behaviour between glulam and carbon fibre reinforced polymer laminates strips, an experimental program using pull-out tests was carried, when the near-surface strengthening technique is applied. Two main variables were studied: the bond length and the type of pull-out test configuration. The instrumentation included the loaded and free-end slips, as well as the pull-out force. Based on the obtained experimental results, and applying an analytical-numerical strategy, the local bond stress-slip relationship was determined. In this work the tests are described, the obtained results are presented and analysed, and the applicability of an inverse analysis to obtain the local bond law is demonstrated.